Defining statesmanship a comparative political theory analysis - Ray, Clyde; IG Publishing Online (Online service). (Lanham, Maryland Lexington Books, 2020)
"A study of ancient, medieval, and modern forms of leadership, this book brings to light qualities of statesmanship that continue to resonate in our current political environment"--Provided by publisher.
Includes bibliographical references (pages 117-131) and index.
Keywords: Electronic books; Political leadership; Statesmanship